Internal audit functions and sustainability audits: Insights from manufacturing firms - Gilbert K. Amoako; Jonas Bawuah; Emmanuel Asafo-Adjei; Catherine Ayimbire (Cogent Business & Management, 2023)
We examined the nexus between four internal audit functions (IAF) and sustainability audits (SA) of manufacturing firms. The specific IAF employed in this study were; risk management practices (RMP), sustainability sensitivity (SS), internal audit effectiveness (IAE) and enactments, policies, standards, systems and procedures (EPS). In line with the four measures of IAE, the study puts forward to investigate four research hypotheses. The explanatory research design and quantitative research approach were applied to achieve the study's objective. A sample of 1340 managers of SMEs were invited to complete a standard questionnaire based on extensive evaluations of prior empirical investigations. The samples were chosen using a straightforward random process from a population of 2495 manufacturing companies. The results were estimated using the partial Least Square Structural Equation Modelling (PLS-SEM) method. Findings from the study divulged that internal audit effectiveness, risk management process and sustainability sensitivity had significant positive relationship with sustainability audits. It is important for the creation of an audit department, the hiring of a permanent internal auditor, the provision of suitable logistics, the training of personnel on the value of internal audit, and the use of internal auditing standards and principles in the report-writing process for an enhanced sustainability audit.
Keywords: M4; M41; M42; Q56; 650; Internal audit effectiveness; partial least squares; risk management practices; sustainability audits; sustainability sensitivity